Prognostic value of RASD1 transcript levels in adult Philadelphia-negative B-cell acute lymphoblastic leukemia. Issue 1 (1st January 2021) - Lu, Run-Qing; Wu, Li-Xin; Zhang, Jing; Qin, Ya-Zhen; Liu, Yan-Rong; Lai, Yue-Yun; Jiang, Hao; Chang, Ying-Jun; Ruan, Guo-Rui; Huang, Xiao-Jun
ABSTRACT: Objectives: Ras-related dexamethasone-induced 1 ( RASD1 ) is abnormally expressed in many solid cancers. However, its potential role in adults with B-cell acute lymphoblastic leukemia (B-ALL) is unclear. Therefore, we aim to clarify the abnormal expression of the tumor-associated biomarker, RASD1, as a potential target for diagnosis and prognosis in adult Philadelphia-negative B-ALL. Methods: The expression of RASD1 was detected with RT-qPCR in 92 adults with de novo Ph-negative B-ALL and 40 healthy controls. The correlation between RASD1 transcript levels and relapse was assessed. Results: RASD1 transcript levels in patients with Ph-negative B-ALL (median 81.76%, range 0.22%-1824.52%) were significantly higher than those in healthy controls (7.59%, 0.46%-38.66%; P <0.0001). Patients with low RASD1 transcript levels had a lower 5-year relapse-free survival (RFS, 47.5% [32.9%, 62.1%] vs. 63.1% [49.0%, 77.2%]; P = 0.012) and a higher 5-year cumulative incidence of relapse (CIR, 52.0% [37.4%, 66.6%] vs. 36.2% [22.2%, 50.2%]; P = 0.013) especially in patients receiving chemotherapy only. Multivariate analysis showed that a low RASD1 transcript level was an independent risk factor for RFS (HR = 2.938 [1.427, 6.047], P = 0.003) and CIR (HR = 3.367 [1.668, 6.796], P = 0.001) in patients with Ph-negative B-ALL. Conclusions: RASD1 transcript levels were significantly higher in patients with Ph-negative B-ALL and a low RASD1 transcript level was independently correlated with increased relapse risk.